The maze of bones - Riordan, Rick (39 clues, 2008)
At the reading of their grandmother's will, Dan and Amy Cahill are given the choice of receiving a million dollars or uncovering the 39 clues hidden around the world that will lead to the source of the family's power, but by taking on the clues, they end up in a dangerous race against their own family members.